The impact of fish oil supplementation in patients with rheumatoid arthritis - Barkoot, Maram; Albejawi, Abdulrahman; Alhadri, Ali; Albalawi, Sahar; Al Awwas, Muayad; Alameer, Mashal; Alshlaqi, Badriah; Alshammary, Anwaar; Alameer, Duaa; Alhawiti, Mashael (International Journal Of Community Medicine And Public Health, 2018)
Many clinical trials of omega-3 fatty acids, supplied as fish oil supplements, have been carried out in rheumatoid arthritis (RA) over the past 3 decades. The current analysis evaluates the influence of omega-3 polyunsaturated fatty acids on clinical results in patients with rheumatoid arthritis. We conducted the current meta-analysis using a comprehensive search of EMBASE, MEDLINE, PubMed, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials till 31 January 2018 for randomized controlled trials that examined the influence of omega-3 PUFAs on clinical results in patients with rheumatoid arthritis. We identified 8 prospective studies that could be included in the meta-analysis. They showed that omega-3 PUFAs had a clear influence on NSAID consumption (SMD −0.52, 95% CI −0.92 to −0.12, p = 0.01) without between-study heterogeneity (I2 = 0%) and in pain (SMD −0.55, 95% CI 0.17–0.027, p = 0.57). The use of omega-3 PUFAs at dosages of >2.7 g/day for more than three months can be effective at decreasing NSAID use in rheumatoid arthritis patients.